The Relationship between Campus Da'wah Institutions (LDK) Activities and Student Religiosity: A Case Study of the Da'wah Corps of the Islamic University of Indonesia (KODISIA) - Faiz, Karman; Aldi, Ujang; Darojat; Azizah, Zahra Nur; Khotimah, Imas (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2025)
This study aims to determine the magnitude and direction of the influence of da'wah activities carried out by the Campus Da'wah Institution (LDK) of the Da'wah Corps of the Islamic University of Indonesia (KODISIA) on the level of religiosity of its members. This study uses a quantitative approach with a field research design. The population consisted of 48 active members of LDK KODISIA in 2017, making it a saturated sample (population study). Data were collected using questionnaires and analyzed using simple linear regression with the help of the SPSS 18.00 program. The results of the simple linear regression analysis showed that da'wah activities did not significantly affect the religiosity of LDK KODISIA students. The correlation value (R) was found to be very low, namely 0.030, with a coefficient of determination (R2) of 0.001 or 0.1%. This shows that the contribution of campus da'wah activities to student religiosity can be ignored. The remaining 99.9% of student religiosity is influenced by other factors. This finding rejects the alternative hypothesis (Ha) and accepts the null hypothesis (H0), implying that LDK KODISIA activities are not a single significant predictor of the religiosity of its members. The implication is that LDK needs to adopt a more holistic approach, exploring and integrating non-formal factors such as social influence, emotional experiences, and intellectual development (e.g., Thouless factors) into their programs to strengthen and internalize religious values more effectively among students.